Legitimidade e conformação da imputação preliminar no modelo constitucional de processo penal - Johnny Wilson Batista Guimarães (2016)
In this thesis we analyze the attribution of a crime to a person during the law enforcement stage, thus before the beginning of a criminal prosecution. From now on we will refer to the police imputation of a crime to an individual before the prosecution decision to press charges as premature charging. We study the grounds, juridical nature, and results of the police premature charging. We also examine the legal framework that grants authority to the police to impute criminal actions to the investigated. From the perspective of the current legal system, we vet the police premature charging, and we propose that only the prosecution is the rightful holder of the opinio delicti. In order to complete the analysis, we utilize the Italian criminal procedure guideline about indagine preliminare. We critique under various optics the truth over which rests the police premature charging, therefore demonstrating its weakness. Furthermore, we evaluate the issuance of provisional remedies based on premature charges along with its harmful and sometimes irreparable effects to the investigated who is deprived of defense. Throughout this research, we assess the police premature charging in light of the criminal law guarantism theory. Under this approach, the premature charging stands out in the evidentiary stage as a mechanism of unjustifiable fundamental rights restriction of the investigated, blurring his defense rights. The police must investigate and elaborate the police report with the utmost fairness, and this fairness is a necessary condition to the concession of provisional remedies that constraints fundamental rights. We address particularly the submission of the police report with criminal charges to the court, the act that manifests the premature charging, as we scrutinize the normativity of the premature charging and the current and undue trend to enhance its effects in prejudice of the defendant.